Significados de los Cuidados Paliativos para miembros de la familia y sus implicaciones para el duelo anticipatorio - da Costa dos Reis, Cristine Gabrielle; Ojeda Ocampo Moré, Carmen Leontina; Menezes, Marina; Ibarra Dobes da Rosa, Estefânia; Campos, Raquel (Pontificia Universidad Católica del Perú, 2022)
This qualitative study aimed to understand the meanings attributed to Palliative Care and its implications for the anticipatory mourning process, from the perspective of family caregivers. Participants were 14 family members of patients in Palliative Care. Participant observation and semi-structured interviews were carried out. The data were analyzed and organized based on the Grounded Theory, using the Atlas.ti 7.5 software. The results showed the meanings attributed to Palliative Care marked by the impact of the treatment proposal, by the emergence of feelings and experiences, and traversed by the specific care requirements, the treatment, and the decision making, generating repercussions in the caregiver’s life. Visualizing the set of meanings attributed during the process permits the support of actions in Palliative Care that recognize elements that constitute anticipatory mourning.

Este estudio cualitativo tuvo como objetivo comprender los significados atribuidos a los Cuidados Paliativos y sus implicaciones en el proceso de duelo anticipatorio, desde la perspectiva de los cuidadores familiares. Participaron 14 familiares de pacientes en Cuidados Paliativos. Se realizó observación participante y entrevistas semiestructuradas. Los datos fueron organizados y analizados teniendo como base la teoría fundamentada. Los resultados mostraron los significados atribuidos a los Cuidados Paliativos marcados por el impacto de la propuesta de tratamiento, por la aparición de sentimientos, experiencias y atravesadas por las demandas específicas de cuidado, tratamiento, y toma de decisiones, generando repercusiones en la vida del cuidador. Visualizar el conjunto de significados atribuidos durante el proceso permite subsidiar las acciones en Cuidados Paliativos que reconozcan elementos constitutivos del duelo anticipatorio.

Cette étude qualitative visait à comprendre les significations attribuées aux Soins Palliatifs et leurs implications dans le processus de deuil anticipé, du point de vue des aidants naturels. Les participants étaient 14 parents de patients en soins palliatifs. L’observation des participants et les entrevues semi-structurées ont été réalisées. Les données ont été analysées et organisées en fonction de la théorie fondée. Les résultats ont montré les significations attribuées aux Soins Palliatifs par l’impact de la proposition de traitement, par l’émergence de sentiments, d’expériences et traversés par les exigences spécifiques des soins traitement et la prise de décision, générant des répercussions sur la vie de l’aidant. Visualiser significations assignées tout au long du processos il permet de subventionner les actions en Soins Palliatifs, qui reconnaissent des éléments constitutifs du deuil anticipé.

Este estudo qualitativo objetivou compreender os significados atribuídos aos Cuidados Paliativos e suas implicações no processo de luto antecipatório, na perspectiva de familiares cuidadores. Participaram 14 familiares de pacientes em Cuidados Paliativos. Realizou-se observação participante e entrevista semiestruturada. Os dados foram analisados e organizados com base na Grounded Theory, com auxílio do software Atlas.ti 7.5. Os resultados evidenciaram os significados atribuídos aos Cuidados Paliativos marcados pelo impacto da proposta do tratamento, pela emergência de sentimentos e experiências, e atravessados pelas demandas específicas de cuidado, do tratamento, e de tomadas de decisão, gerando repercussões na vida do cuidador. Visibilizar o conjunto de significados atribuídos no decorrer do processo permite subsidiar ações em Cuidados Paliativos que reconheçam elementos constitutivos do luto antecipatório.
Meanings of Palliative Care for family members and its implications for anticipatory mourning
Signification des soins palliatifs pour les membres de la famille et ses implications pour le deuil anticipé
Keywords: Palliative care; Caregivers; Family caregivers; Mourning; Anticipatory mourning; Cuidados Paliativos; Cuidadores; Cuidadores familiares; Luto; Duelo anticipatorio; Soins Palliatifs; Les soignants; Les aidants naturels; Deuil; Deuil anticipé; Cuidados Paliativos; Cuidadores; Cuidadores familiares; Luto; Luto antecipatório; https://purl.org/pe-repo/ocde/ford#5.01.00